Data Flow Design of System Sales Beverage Products for Small Medium Enterprises - Pabara, Arauna Rangan; Batmetan, Johan Reimon (International Journal of Information Technology and Education, 2022)
This research aims to design a ballo’ sales information system in Lembang Rantebua. The method used in this research is a qualitative method. The data collection technique is by interview and literature study. The data analysis method used in this research is descriptive analysis. Regarding the sale of ballo’ in Lembang Rantebua, it is carried out to take advantage of an information technology by designing WEB-based sales of ballo’ in Lembang Rantebua. By designing a design that starts from a context diagram, DFD level 0, DFD level 1 and DFD level 2 regarding Ballo’ sales. is in Lembang Rantebua.